Safe contact-based robot active search using Bayesian optimization and control barrier functions - Vinter-Hviid, Frederik; Sloth, Christoffer; Savarimuthu, Thiusius Rajeeth; Iturrate, Iñigo (Frontiers in Robotics and AI, 2024)
In robotics, active exploration and learning in uncertain environments must take into account safety, as the robot may otherwise damage itself or its surroundings. This paper presents a method for safe active search using Bayesian Optimization and Control Barrier Functions. As robot paths undertaken during sampling are continuous, we consider an Informative Continuous Expected Improvement acquisition function. To safely bound the contact forces between the robot and its surroundings, we leverage Exponential Control Barrier Functions, utilizing the derivative of the force in the contact model to increase robustness to uncertainty in the contact boundary.Our approach is demonstrated on a fully autonomous robot for ultrasound scanning of rheumatoid arthritis. Here, active search is a critical component of ensuring high image quality. Furthermore, bounded contact forces between the ultrasound probe and the patient ensure patient safety and better scan quality.To the best of our knowledge, our results are both the first demonstration of safe active search on a fully autonomous robot for ultrasound scanning of rheumatoid arthritis, and the first experimental evaluation of bounding contact forces in the context of medical robotics using Control Barrier Functions. The results show that, when search time is limited to under 60 s, Informative Continuous Expected Improvement leads to a 92% success, a 13% improvement compared to Expected Improvement. Meanwhile, Exponential Control Barrier Functions are able to limit the force applied by the robot to under 5N, even in cases where the contact boundary is specified incorrectly by -1 or +4 mm.